CERTAIN FORMS OF EXPRESSION OF JUDICIAL PRECEDENT - R. Gubaydullin, Aydar; V. Kurnosova, Valeriya (Gênero & Direito, 2019)
The relevance of the studied issues is associated with the increased interaction of the legal systems of our time. The research methodology is based on the dialectic and the systematic approach that follows from it. The article authors take into account the pluralism of the concepts involved in the study. The classic case law is applied to the Anglo-Saxon legal family. The terms judicial precedent and judicial practice are understood synonymously, but only if the judicial practice is created by the highest judicial instances.